Not part of my routine: a qualitative study of use and understanding of UV forecast information and the SunSmart app - Anna Nicholson; Michael Murphy; Heather Walker; Rick Tinker; Suzanne Dobbinson (BMC, 2019)
Abstract Background The Ultraviolet (UV) Index provides a reliable means of monitoring the strength of UV radiation at the Earth's surface, which can be used to indicate the potential for skin damage. This qualitative study aims to examine public understanding of the UV Index among Australians who routinely use UV forecast information as well as those who do not. Methods Recent use of the SunSmart app (a popular mobile and tablet app that provides UV forecast information) served as a proxy for use of UV forecast information. Six focus groups were conducted with 'new users', who trialled the SunSmart app for the first time in the two weeks preceding the group discussion. In addition, 15 in-depth interviews were conducted with 'existing users', who routinely used the SunSmart app. Thematic discourse analysis was undertaken to compare views and experiences. Results Misperceptions about UV radiation were common. Participants learnt new information about UV radiation, the UV Index, and the times of the day that sun protection is recommended. Among adults who were using UV forecast information for the first time, this learning rarely translated to new behaviours; for these participants, the UV Index forecast information and recommendations were inconsistent with their own observation of the weather and subsequent judgement about their propensity to burn. Thus new users considered the UV forecast information to be overly cautious. In contrast, existing users recognised their inability to judge the UV Index level; for these participants, UV forecast information provided by the SunSmart app was incorporated into their daily routines and used to inform their sun protection behaviours. Conclusions/implications No matter how broadly UV forecast information is promoted, it is unlikely to improve sun protection behaviours across the Victorian population due to the low level of basic understanding of UV radiation. Public education strategies that correct the commonly held misperception that temperature and/or sunshine can reliably predict the potential for UV damage are required. Improved public awareness about UV radiation and how the UV Index can be used to prevent skin cancer may help Australians to develop more effective sun protection habits.